2019
DOI: 10.1002/eat.23182
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence and constipation in adolescent patients with anorexia nervosa—Results of a multicenter study from a German web‐based registry for children and adolescents with anorexia nervosa

Abstract: Objective Nocturnal enuresis (NE), daytime urinary incontinence (DUI), and fecal incontinence (FI) are common disorders in childhood and are frequently accompanied by comorbid psychiatric disorders. Despite a high association between urinary and fecal incontinence with psychiatric and neurodevelopmental disorders, research on comorbidity between incontinence and anorexia nervosa (AN) remains scarce. Yet, it is well known that somatic consequences of AN include metabolic and gastrointestinal disorders. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Inconsistent findings have been reported by studies of small clinical samples that examined if the prevalence of incontinence is greater in adolescents diagnosed with anorexia compared with the general population. 19 Bedwetting was the least prevalent exposure, which might explain why we found fewer (or only weak evidence of) associations with the mental health problems. We also found few associations between soiling and mental health outcomes.…”
Section: Discussionmentioning
confidence: 75%
“…Inconsistent findings have been reported by studies of small clinical samples that examined if the prevalence of incontinence is greater in adolescents diagnosed with anorexia compared with the general population. 19 Bedwetting was the least prevalent exposure, which might explain why we found fewer (or only weak evidence of) associations with the mental health problems. We also found few associations between soiling and mental health outcomes.…”
Section: Discussionmentioning
confidence: 75%
“…Again, however, colonic transit time did not correlate with BMI, self‐reported symptoms, caloric intake on admission, or laxative use. Other studies have also corroborated a lack of correlation between self‐reported constipation and BMI (Mattheus et al, 2020; Sileri et al, 2014). Self‐reports of constipation and duration of ED were found to correlate in one study (Sileri et al, 2014).…”
Section: Resultsmentioning
confidence: 82%
“…Other studies have also corroborated a lack of correlation between self-reported constipation and BMI (Mattheus et al, 2020;Sileri et al, 2014). Self-reports of constipation and duration of ED were found to correlate in one study (Sileri et al, 2014).…”
Section: Intestinal Transitmentioning
confidence: 84%
“…Constipation is another reason why both subtypes of people with AN might seek ED care. All people with AN have markedly prolonged colonic transit time as a result of their weight loss and are at risk for constipation [ 56 ], occurring in approximately 30% of people with AN [ 57 ]. Thus, these patients can suffer with constipation especially those with more severe AN at the beginning of refeeding.…”
Section: Medical Complicationsmentioning
confidence: 99%